2011
DOI: 10.1016/j.resp.2011.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bronchial blood flow and conductance on pulmonary function in stable systolic heart failure

Abstract: The aim of this study was to determine the relationship between airway blood flow (Q̇aw), airway conductance (Gf-aw) and pulmonary function in patients with stable HF. 12 controls (CTRL: age=63±9yr, FVC=98±15%pred, LVEF=61±6%) (all data presented as mean±SD), 16 patients with mild HF (HF-A, NYHA I–II: age=64±9yr, FVC=90±17%pred, LVEF=28±6%), and 14 patients with moderate/severe HF (HF-B, NYHA III–IV: age=65±6yr, FVC=84±12%pred, LVEF=26±6%) were studied. Q̇aw was assessed using soluble gas measurements; perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…However, as can be seen in Table 2, the single breath method tends to yield higher DLNO/DLCO ratios than that of the rebreathe method (presently, mean 5.39 ± 0.43 for single breath vs. 3.58 ± 0.59 for rebreathe), such that approaching the asymptote is not usually an issue. The observation that DLNO/DLCO is slightly higher using the single breath method is found in our laboratory and others (Ceridon et al, 2010; Ceridon et al, 2011; Coffman et al, 2016; Zavorsky and Lands, 2005; Zavorsky and Murias, 2006). …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, as can be seen in Table 2, the single breath method tends to yield higher DLNO/DLCO ratios than that of the rebreathe method (presently, mean 5.39 ± 0.43 for single breath vs. 3.58 ± 0.59 for rebreathe), such that approaching the asymptote is not usually an issue. The observation that DLNO/DLCO is slightly higher using the single breath method is found in our laboratory and others (Ceridon et al, 2010; Ceridon et al, 2011; Coffman et al, 2016; Zavorsky and Lands, 2005; Zavorsky and Murias, 2006). …”
Section: Discussionsupporting
confidence: 83%
“…From both of these studies, our laboratory has concluded that the θ CO equation described by Reeves and Park is ideal, while the optimal α value is dependent on the technique used; ~2.26 for rebreathe and ~4.40 for single breath. This difference can be understood by recognizing that the single breath method, in our laboratory and others, often yields DLNO values somewhat higher than the rebreathe method (Ceridon et al, 2010; Ceridon et al, 2011; Coffman et al, 2016; Snyder et al, 2007; Zavorsky et al, 2014; Zavorsky and Murias, 2006; Zavorsky et al, 2004). Of note, while this inconsistency in DLNO values between the two methods in not completely understood, it is not the focus of this manuscript.…”
Section: Methodsmentioning
confidence: 87%
“…cardiomegaly); the erectile nature of an engorged pulmonary and/or bronchial vasculature; the development of pulmonary interstitial oedema, particularly during exercise; and remodelling of the lung parenchyma due to elevated circulating cytokines and/or chronic hydrostatic insult [18, 41, 5052]. Although the mechanisms for the lower C L,dyn have been well described in HF, we also noted that compliance of the chest wall in these patients was lower (~18%) than in control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…5 Structural and functional alterations of the lungs in HF are well described 5,6 and correlate to HF severity and patient survival. They are linked neurohumourally and hemodynamically (e.g.…”
Section: Introductionmentioning
confidence: 99%